Hematopoietic Stem Cell Transplantation in Primary Immunodeficiencies Beyond Severe Combined Immunodeficiency. (26th December 2018) - Freeman, Alexandra F
Abstract: Hematopoietic stem cell transplantation (HSCT) has been the standard of care for infants with severe combined immunodeficiency (SCID) for several decades due to the dismal prognosis early in life without immune reconstitution. In recent years, as HSCT conditioning regimens and supportive care have greatly improved, HSCT is gaining in acceptance for more non-SCID primary immunodeficiencies (PIDs) and outside the early childhood period. In addition, potential donor options for non-SCID PIDs are expanding with increasing success for haploidentical donor transplants. In this brief report of a presentation at the PIDS-St. Jude 2018 conference, PIDs for which transplants are increasingly performed outside of early childhood will be discussed.